The Effect of Career Development, Performance of Buru Regency Food Security Service Government Employees - Masna Hatuwe; Muspiha Muspiha (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
Career development can be realized if planned properly, there are opportunities for promotion, motivational support is carried out by the leadership, awards, opportunities for growth and promotion for an employee Career development has an influence relationship with Employee Performance Employee performance can be measured and realized in the target achieved maximally with the support of the ability to complete the work carefully and good cooperation is established in the supervision of the help each other in overcoming various problems and difficulties in an atmosphere family and the support of colleagues in working in implementing determined decisions. Career development has an influence relationship with employee performance at the Buru District Food Security Service. How big is the relationship and The significance of career policy on performance is the aim of this study. The research was carried out at the Food Security Office of Buru Regency. Data sources are primary and secondary data. The analytical tool used is Linear Regression Simple Y= a + bx - e get the equation of function Y = 38.735-239X+...e The hypothesis which states that Career Development has an effect significant effect on employee performance at the Buru District Food Security Service not accepted. Based on the hypothesis test (Parisial-t-test) t- hitmg>t-tb (0.486 < 1.73406) then the hypothesis is rejected and it is found that Career Development has an effect not significant to the performance of employees at the District Food Security Service Buru,